The level of specific motor properties in the individual phases of the menstrual cycle among young sportswomen practicing sprints = Poziom określonych właściwości motorycznych w poszczególnych fazach cyklu menstruacyjnego wśród młodych sportsmenek uprawiających sprinty - Vrublevskiy, Evgeny; Kozhedub, Marina (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The aim of the article is to assess the level of selected motor properties in particular phases of the sexual cycle among sprinters. The material used in this study was collected during the gathering of the Belarus national team in 2016, among women practicing short runs. 58 Female athletes, aged 18 to 25, regularly trained sprints 5-6 times a week, each time for 2 hours a day. They all had the master or first sports class. The average internship period was 7 years. The following measurements were taken: power, speed, and jumping.
Keywords: motor features; menstrual cycle; sprinter; cechy motoryczne; cykl menstruacyjny